Malaysian Public Private Partnership Projects: Project Success Definition - Ahamd, Usman; Bt Ibrahim, Yusnidah; Bt Abu Bakar, Arpah (International Journal of Engineering and Technology, 2018)
In last few decades, many governments have been using Public Private Partnership (PPP) as a tool to provide infrastructure and public services. Most of PPP projects achieved the objectives whereas, a few are underachieved. Besides, prior literature does not provide robust definition of success for PPP projects. Although, project management literature defines the general definition of project success and explains success as variable. However, due to the distinct nature of PPP projects there is a need to redefine the PPP project success. Therefore, this study aims to provide robust definition of the success of PPP project based on distinct nature of PPP project. To achieve the objective, this study has adopted phenomenological research method and conducted semi-structured interviews. Thematic analysis has been carried out by using ATLAS-ti 8.0 to arrange interviewsâ€™ data. Based on interviews, arrangements of two types of PPP projects, Build Lease Maintain and Transfer (BLMT) and Lease Maintain and Transfer (LMT) have been explained that leads to the development of the success criteria for PPP projects. The results reveal that one of the dimensions of success i.e. preparing for future is not valid to measure success for PPP projects.Â Â